Methodological recommendations for choreographic training of young acrobats - Shelgacheva, A. M.; Bezhentseva, L. M.; Kim, D. S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to provide a scientific basis for the efficacy of the application of the method of choreographic training for young acrobats during the initial training phase.